Analysis of near cortex versus both cortex fixation in bone fracture surgery : a finite element study - Loh, Chuan Kui (2019)
The locking compression plate (LCP) is an implant used to bridge bone fractures and promotes bone fracture healing by callus formation through interfragmentary motion. However, due to its close proximity to the bone, the LCP construct may be too stiff and would result in suboptimal interfragmentary motion and subsequently, poor callus formation and atrophic non-union. To reduce fracture fixation stiffness, the drilling of elongated trapezoid and figure-of-8 holes in the near cortex of the bone was proposed to reduce the construct stiffness without significant decrease in strength. Finite element analyses (FEA) were conducted on the axial compression, four-point bending and torsional loading of the constructs to simulate the construct deformation. The simulated results were then compared to that of the physical experiments to validate the finite element (FE) models. In previous work, validation of the FE models was achieved only to a certain extent. Hence, the objective of the current study is to reduce the FEA-experiment deviation by improving the contact interface modelling of FE models. Conclusively, the FE models created for the elastic axial compression of the control and figure-of-8 constructs and torsional loading were validated with the experimental results. Additionally, the simulations corroborated the hypothesis that introducing elongated holes in the near cortex of the bone reduces the construct stiffness without compromising its strength. The study serves as a preliminary foundation for future work in simulating plate-bone fixation with FEA by studying the impact of contact modelling on plate-bone fixation FE model optimization. Furthermore, the validated FE models could be utilized as a predictive simulation model to investigate other hypotheses to reduce fracture fixation stiffness.